2022
DOI: 10.1021/acscatal.2c01654
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Electrolysis via Surface-Engineering Electrografted Pyridines on Silver Catalysts

Abstract: The electrochemical reduction of carbon dioxide (CO2) to value-added materials has received considerable attention. Both bulk transition metal catalysts, and molecular catalysts affixed to conductive non-catalytic solid supports, represents a promising approach towards electroreduction of CO2. Here, we report a combined silver (Ag) and pyridine catalyst through a green and irreversible electrografting process, which demonstrates enhanced CO2 conversion versus the individual counterparts. We find by tailoring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 116 publications
1
32
0
Order By: Relevance
“…Electrografting molecules permits the growth of an organic moiety onto an electrode surface through the formation of radical species with concomitant electron transfer to or from molecules containing suitable activating groups, such as diazoniums or iodoniums (Figure c) . This process affords an organic coating with strong adhesion to many conductive substrates, such as Cu, Ag, glassy carbon, and stainless steel, that can withstand sonication even in organic solvents and could therefore be a promising alternative strategy to prolong catalytic performance. Unfortunately, reports using ethynyl and azide aryl radical precursors on copper surfaces have shown little promise for achieving significant enhancement of CO 2 R selectivity, likely due to the conflation of effects from the highly functionalized film and the anodic grafting mechanism employed. Alternative methods that allow a decoupling of the effects of deposition techniques and film functionalization are therefore desirable to obtain a greater understanding of the mechanism by which grafted films affect selectivity.…”
mentioning
confidence: 99%
“…Electrografting molecules permits the growth of an organic moiety onto an electrode surface through the formation of radical species with concomitant electron transfer to or from molecules containing suitable activating groups, such as diazoniums or iodoniums (Figure c) . This process affords an organic coating with strong adhesion to many conductive substrates, such as Cu, Ag, glassy carbon, and stainless steel, that can withstand sonication even in organic solvents and could therefore be a promising alternative strategy to prolong catalytic performance. Unfortunately, reports using ethynyl and azide aryl radical precursors on copper surfaces have shown little promise for achieving significant enhancement of CO 2 R selectivity, likely due to the conflation of effects from the highly functionalized film and the anodic grafting mechanism employed. Alternative methods that allow a decoupling of the effects of deposition techniques and film functionalization are therefore desirable to obtain a greater understanding of the mechanism by which grafted films affect selectivity.…”
mentioning
confidence: 99%
“…To date, the highest Faradaic efficiency (FE) for yielding CH 4 , C 2 H 4 , and C 2+ products based on MOF electrocatalysts reaches >80%, ,, >50%, ,, and 80%, respectively (Figure and Table ). Previous reports revealed that the electrocatalysts with Au, , Ag, Co, or Ni active sites tend to generate CO as the main product, and those with In , or Sn , result in formate. Since the copper center has a negative adsorption energy for an essential intermediate *CO and a positive adsorption energy for *H, , Cu-based catalysts show an enormous advantage in electrochemical reduction of CO 2 to the high value-added products, such as hydrocarbons and carbon oxygenates ( i .…”
Section: Selectivity Controlmentioning
confidence: 99%
“…[5][6][7] However, the state-of-the-art CO 2 electrolysis usually uses pure CO 2 as the feed, while CO 2 is diluted in most industrial sources (<20% for flue gases from blast furnaces and post-combustion power plants [8][9][10] ). 5,[11][12][13][14][15][16][17][18][19][20][21] When implemented in practice, CO 2 electrolysis requires costly upstream CO 2 capture processes 22,23 to concentrate CO 2 , and an energy-intensive product separation process 24,25 to recycle CO 2 and concentrate product streams. In addition, gaseous CO 2 reacts with hydroxide ions generated within CO 2 electroreduction systems to form (bi)carbonate.…”
Section: Kailun Yangmentioning
confidence: 99%